Tanggung Jawab Negara dalam Kebijakan Bantuan Hukum bagi Masyarakat Miskin Menurut Undang-Undang Nomor 16 Tahun 2011 dalam Perspektif Siyāsah Tanfīdziyyah - Imbi Akma Pala; A. Kumedi Ja'far; Rudi Santoso (Kartika: Jurnal Studi Keislaman, 2026)
Access to justice constitutes a constitutional right of every citizen, however economically disadvantaged communities continue to face significant barriers in obtaining adequate legal protection. This condition prompted the Indonesian government to enact Law Number 16 of 2011 on Legal Aid as a legal instrument aimed at protecting underprivileged groups. This study seeks to examine the implementation of state responsibility in legal aid policies for the poor under Law Number 16 of 2011 and to analyze its relevance from the perspective of Siyāsah Tanfīdziyyah. This research employs a normative legal method using statutory, conceptual, and siyasah approaches. Data were collected through library research utilizing primary and secondary legal materials and analyzed descriptively and analytically. The findings reveal that legal aid policy represents a concrete manifestation of the state's responsibility to ensure access to justice and the protection of citizens' constitutional rights. Nevertheless, its implementation continues to encounter challenges, including unequal distribution of legal aid organizations, limited public legal awareness, and restricted access to legal services in certain regions. From the perspective of Siyāsah Tanfīdziyyah, legal aid policy embodies the principles of al-'adālah (justice), al-maṣlaḥah al-'āmmah (public welfare), and governmental trust, positioning the state as the primary actor responsible for realizing justice and social welfare within society